Associations between breastfeeding and self-reported experience of the “10 Steps to Successful Breastfeeding”: a cross-sectional and longitudinal study of maternity clinic practices in Cyprus - Mary Economou; Ourania Kolokotroni; Irene Paphiti-Demetriou; Christiana Kouta; Ekaterini Lambrinou; Eleni Hadjigeorgiou; Vasiliki Hadjiona; Nicos Middleton (Frontiers in Global Women's Health)
ObjectiveTo assess the implementation of the “10 Steps for Successful Breastfeeding” and explore associations with any Breastfeeding (BF) and Exclusive Breastfeeding (EBF) initiation and continuation.MethodsImplementation of the 10 Steps was assessed based on a consecutive sample of 568 mothers’ self-reported experience across all public (N = 5) and 29 (of 35) private maternity clinics using the WHO/UNICEF BFHI questionnaire (Section 4) within the first 24–48 h after birth. BF and EBF were estimated within 48 h after birth as well as at 1st, 4th and 6th month based on a self-reported current status method. Associations with initiation and continuation of any BF and EBF up to the 6th month were explored in logistic regression after adjusting for potential confounders. Associations were explored with individual steps as well as the overall experience, operationalized as the sum score of full, partial or no implementation of each item, with the exception of Step 6 (exclusive breastfeeding).ResultsAt mean score 6.2 (SD = 2.7), the overall 10 Steps experience was low (theoretical range 0–14), even among those who breastfed exclusively (M = 7.7, SD = 2.0). EBF and BF initiation and continuation showed a stepwise association with self-reported experience of the 10 Steps. Across quartiles of increasing scores within 48 h after birth, the prevalence of EBF was 7.5%, 14.4%, 19.0%, and 34.2%. Mothers who experienced full or partial implementation of Step 4 (i.e., early initiation with skin-to-skin) were more likely to continue BF and EBF up to the 4th month, while use of pacifiers (Step 9) was more likely to have an adverse effect on breastfeeding continuation and exclusivity.ConclusionThe BFIH's “10 Steps” are associated with BF initiation while certain practices seem to be more strongly associated with exclusivity and continuation of breastfeeding up to the sixth month. While breastfeeding intention may determine the experience of the 10 Steps, this also suggests that maternity care practices can have a supportive role for mothers to succeed their intentions to BF and EBF.